Total internal reflection fluorescence anisotropy imaging microscopy: setup, calibration, and data processing for protein polymerization measurements in living cells. (19th December 2017) - Ströhl, Florian; Wong, Hovy H W; Holt, Christine E; Kaminski, Clemens F
Abstract: Fluorescence anisotropy imaging microscopy (FAIM) measures the depolarization properties of fluorophores to deduce molecular changes in their environment. For successful FAIM, several design principles have to be considered and a thorough system-specific calibration protocol is paramount. One important calibration parameter is the G factor, which describes the system-induced errors for different polarization states of light. The determination and calibration of the G factor is discussed in detail in this article. We present a novel measurement strategy, which is particularly suitable for FAIM with high numerical aperture objectives operating in TIRF illumination mode. The method makes use of evanescent fields that excite the sample with a polarization direction perpendicular to the image plane. Furthermore, we have developed an ImageJ/Fiji plugin, AniCalc, for FAIM data processing. We demonstrate the capabilities of our TIRF-FAIM system by measuring β -actin polymerization in human embryonic kidney cells and in retinal neurons.